2023
DOI: 10.3390/ijerph20032364
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants and Prevalence of Antenatal Depression among Women in Rural Bangladesh: A Cross-Sectional Study

Abstract: The prevalence of antenatal depression in Bangladesh ranges from 18 to 33%. Antenatal depression has negative impacts on the mother and child such as suicidal ideations, low birth weight, and impaired fetal development. This cross-sectional study aims to determine the prevalence and social determinants of antenatal depression in rural Sylhet, Bangladesh. Data were collected from 235 pregnant women between March and November 2021. The validated Bangla Edinburgh Postnatal Depression Scale was used to measure ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
2
3
1
Order By: Relevance
“…While some studies have identified family support and a preference for the male gender within families as significant contributing factors to prenatal depression (12, 13), this particular study did not observe such associations. It suggests that with the progression of time, contemporary family members may be more attentive and supportive of pregnant mothers than in the past.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…While some studies have identified family support and a preference for the male gender within families as significant contributing factors to prenatal depression (12, 13), this particular study did not observe such associations. It suggests that with the progression of time, contemporary family members may be more attentive and supportive of pregnant mothers than in the past.…”
Section: Discussioncontrasting
confidence: 93%
“…These two groups of women are more likely to be the victims of intimate partner violence (27). This study found intimate partner violence as a significant contributing factor to antenatal depression which is similar to the study conducted by Peltzer et al in Thailand and Insan et al in Bangladesh (12, 28).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations